Reforming Education through Curriculum Evaluation, Challenges and Future Directions - Suhadha, Abdul Karim; Rusman; Kolek, Deodatus; Mulyadi, Dhaffa Muhamad Dzikri (Proceeding International Conference on Education, 2025)
All countries agree that education is the main foundation for national development. Curriculum evaluation is a key component in the process of sustainable education reform. It improves the effectiveness, efficiency, equity, and relevance of the education system, of which the curriculum is central. The success of reform depends heavily on effective curriculum planning, implementation, and evaluation. This article discusses the strategic role of curriculum evaluation in driving change in the education system, focusing on the Indonesian context and its global relevance. Through a literature review of various relevant studies and sources, it is found that the main challenges lie in limited resources, low evaluative teacher competency, and the gap between policy and implementation. On the other hand, the use of digital technology, formative assessment, and multi-stakeholder involvement are potential future directions. This article recommends strengthening data-based evaluation capacity, cross-sector collaboration, and the integration of evaluation into the curriculum planning cycle. These findings are expected to contribute to the development of an adaptive, participatory, and contextual curriculum evaluation model to meet the demands of 21st-century education.